2018
DOI: 10.1007/s11605-018-3707-z
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Emergency Department Utilization and Admission in Patients with Colorectal Cancer

Abstract: Over half of privately insured patients undergoing treatment for colorectal cancer will visit the ED within 12 months of diagnosis. Within this group, we identify common factors for a high-risk subset of patients with three or more ED visits who account for over half of all ED visits and a third of all admissions. These patients could potentially be targeted with alternative management strategies in the outpatient setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 23 publications
3
14
0
1
Order By: Relevance
“…One study in colorectal cancer reported that non-White race was associated with an increase in ED visits and hospitalizations but was not specific to diabetes. 41 Another study in breast cancer reported that Black women were twice as likely to have a hospitalization for any cause after adjusting for confounders. 42 Finally, a study of prostate cancer survivors found that Black and Hispanic men were more likely than NHW men to have an ED visit and less likely to have outpatient visits.…”
Section: Discussionmentioning
confidence: 99%
“…One study in colorectal cancer reported that non-White race was associated with an increase in ED visits and hospitalizations but was not specific to diabetes. 41 Another study in breast cancer reported that Black women were twice as likely to have a hospitalization for any cause after adjusting for confounders. 42 Finally, a study of prostate cancer survivors found that Black and Hispanic men were more likely than NHW men to have an ED visit and less likely to have outpatient visits.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it is not possible to determine whether our results are influenced by population variables (race, cultural level, pluripathology, etc.) (26,27) or by organizational variables in the health system where the study was conducted. Considering these limitations, we can conclude that CRC patients whose first contact with the hospital was via the Emergency Department present more advanced stages of the disease and independently predicted poorer survival rates than those with a scheduled visit.…”
Section: Discussionmentioning
confidence: 99%
“…Deidentified administrative claims data from OptumLabs Data Warehouse include medical and pharmacy claims, laboratory results, and enrollment records for >88 million privately insured individuals during the study period. The database contains enrollees with a diverse mixture of ages and ethnicities across all 50 states in the United States 5 and has been used to evaluate health care expenditures and usage in oncology populations 6‐9 . The institutional review board of the University of Alabama at Birmingham approved our study.…”
Section: Methodsmentioning
confidence: 99%
“…The database contains enrollees with a diverse mixture of ages and ethnicities across all 50 states in the United States 5 and has been used to evaluate health care expenditures and usage in oncology populations. [6][7][8][9] The institutional review board of the University of Alabama at Birmingham approved our study.…”
Section: Data Sourcementioning
confidence: 99%